THE IMPACT OF COMMUNICATION FEATURES ON THE MENTAL HEALTH OF HIGHER EDUCATION STUDENTS DURING THE WAR - Гозак, Світлана; Єлізарова, Олена; Станкевич, Тетяна; Чорна, Валентина; Товкун, Лідія; Лебединець, Наталія; Парац, Алла; Бондар, Олександра (SWorldJournal, 2024)
The article examined the impact of communication on students' mental health during wartime. The study found that 71.8% of male and 64.0% of female students communicated regularly. More than half reported difficulties communicating with their fellow stude